Respon Pertumbuhan Cabai Katokkon (Capsicum Chinese Jacq) Terhadap Pemberian Ekstrak Bawang Merah - Givani Sapan Tandiayu; Lestari M.P Alibasyah; Aan Febriawan; Musdalifah Nurdin; Vita Indri Febriani; Amalia Buntu (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the growth response of Katokkon chili plants to the administration of shallot extract. This type of research is an experiment using a quantitative approach method carried out in the form of experiments arranged in a Completely Randomized Design (CRD). This design is carried out with a single treatment consisting of 5 treatment levels, the treatment codes to be tested are: B0: control / no treatment, B1: 7% shallot extract, B2: 14% shallot extract, B3: 21% shallot extract and B4: 28% shallot extract which treatments were repeated 3 times so that there were 15 experimental arrangements. The parameters observed were plant height, number of leaves and stem diameter. Data analysis used the ANOVA test and continued with the BNT test. The results showed that the shallot extract treatment had a significant effect on the growth of Katokkon chili plants in the parameters of plant height and number of leaves. The best treatment was obtained at a concentration of 14% and had no significant effect on stem diameter.